2019
DOI: 10.1039/c9ew00384c
|View full text |Cite
|
Sign up to set email alerts
|

Screen versus cyclone for improved capacity and robustness for sidestream and mainstream deammonification

Abstract: Combining physical and metabolic selection allowed for determination of ideal operational conditions and capacity gain in full-scale deammonification systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…To evaluate the hydrocyclone for its ability to retain the slow-growing AMX a mass balance and microbiome analysis were completed (Figure 1B). The biomass retention of AMX, AOB, and NOB (i.e., ηorganism) was calculated in Equation ( 1) [18], where r describes the volumetric activity rate in underflow and overflow as kg N m −3 d −1 . In order to evaluate the sludge/biomass separation in the hydrocyclone, the periods were examined for similar NLR, according to the statistical analysis described below.…”
Section: Reactor Operation and Process Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the hydrocyclone for its ability to retain the slow-growing AMX a mass balance and microbiome analysis were completed (Figure 1B). The biomass retention of AMX, AOB, and NOB (i.e., ηorganism) was calculated in Equation ( 1) [18], where r describes the volumetric activity rate in underflow and overflow as kg N m −3 d −1 . In order to evaluate the sludge/biomass separation in the hydrocyclone, the periods were examined for similar NLR, according to the statistical analysis described below.…”
Section: Reactor Operation and Process Evaluationmentioning
confidence: 99%
“…Biomass separation strategies such as hydrocyclones or screens allow for process intensification and higher NLR of 0.5-1.0 kg N m −3 d −1 [17]. Anaerobic ammonia-oxidizing bacteria retention can be achieved by various separation strategies that rely on the density difference of bacterial flocs [18]. It is known that AMX aggregate in dense granules of 100-300 µm while AOB and NOB tend to form flocs >100 µm with lower density [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Which could indicate that the S-SBR was limited by AMX rather than AOB. Past studies discussed that the anammox conversion could be enhanced when using an external selector such as a sieve or a hydrocyclone 42 . In the MEDIA, it was observed that the biofilm on the plastic media was coloured blackish, similar to the G-SBR, indicating heterotrophic growth.…”
Section: Stable Operationmentioning
confidence: 99%
“…With the AMX biomass in small flocs in suspension, biomass retention in the biological reactor was only achieved by gravity. It has been suggested that an external selector could enhance the removal efficiency of suspended sludge deammonification technologies by either using a hydrocyclone or a sieve 42 . Overall, it was found that an NRR of 0.30 kgN m -3 d -1 could be maintained at an average temperature of 17°C, implying that the deammonification technologies are robust enough to cope with sudden heat-loss or seasonal temperature fluctuations.…”
Section: Stable Operationmentioning
confidence: 99%